Pengembangan Bahan Ajar Dengan Model Dick, Carey & Carey Pada Mata Pelajaran IPA Kelas XI SMK Negeri 5 Palu - Risma Ganda Hutabarat; Marungkil Pasaribu; I Komang Werdhiana (Mitra Sains, 2015)
The research aims at developing Natural Science Subject Instructional packages of year XI Semester 1 SMK Negeri 5 Palu by employing Dick, Carey & Carey Model. The research employed Research Development (R&D) design. The instructional package drafts that have been previously developed were validated by a content expert, a design expert, and a media expert. The revised version of the packages were tried out into three different subjects; individual, small group, and big group which contained 25 students and 1 teacher. Questionnaire designed in Likert Scale was used as the instrument of data collection. Suggestion, input and comment during consultation period were also noted and used to compliment the collected data from the questionnaire. The results of the data analysis show that 1) the instructional materials product score ranges from 81.33% to 83.80% indicating that the instructional material is classified Good and Very Good, 2) the teacher’s book product score ranges from 80.00% to 91.25% indicating that the teacher’s book is classified Good and Very Good, 3) the student’s book product score ranges from 80.00% to 94.67% indicating that the student’s book is classified Good and Very Good. Based on Kuswadi’s argument (in Sudarman, 2006) if the developed instructional packages scored higher than 71%, the products are ready and valid to be used. The achievement of the students, between the pretest and the posttest, during the instructional materials try out is different significantly calculated by applying t-test formula. It implies that the instructional packages have been valid and ready to be used.